Initial pore distribution characteristics and crack failure development of cemented tailings backfill under low impact amplitude - Zheng, Di; Liu, Guangsheng; Guo, Lijie; Yang, Xiaocong; Wu, Shan; Zhao, Yue (Frontiers in Earth Science, 2023)
In this paper, the computerized tomography (CT) and Split Hopkinson Pressure Bar (SHPB) tests were conducted to explore the initial pore distribution characteristics of the cemented tailings backfill (CTB) and the development of the crack under low impact amplitude. SHPB tests were conducted with impact amplitudes of 34, 37, and 39 mV, respectively. Results show that the initial pores of CTB were steadily distributed with the height of CTB. The CTB contained many initial pores with similar pore size distribution characteristics, and the largest number of pores is between 0.1 and 0.3mm. Most of the cracks in CTB after low impact amplitude develop and expand along the initial pores, and the damage of CTB mainly exists in shear cracks. A dependence has been established that the dynamic uniaxial compressive strength of the CTB increases, the total crack volume first increases and then decreases, and the number of cracks increases as the impact amplitude increases. The research results can provide a valuable reference for the dynamic performance of CTB under low impact amplitude and the design of mining backfill.